BRAKE: Biometric Resilient Authenticated Key Exchange - Pia Bauspieb; Tjerand Silde; Matej Poljuha; Alexandre Tullot; Anamaria Costache; Christian Rathgeb; Jascha Kolberg; Christoph Busch (IEEE Access, 2024)
Biometric data are uniquely suited for connecting individuals to their digital identities. Deriving cryptographic key exchange from successful biometric authentication therefore gives an additional layer of trust compared to password-authenticated key exchange. However, biometric data are sensitive personal data that need to be protected on a long-term basis. Furthermore, efficient feature extraction and comparison components resulting in high intra-subject tolerance and inter-subject distinguishability, documented with good biometric performance, need to be applied in order to prevent zero-effort impersonation attacks. In this work, we present a novel protocol for Biometric Resilient Authenticated Key Exchange that fulfils the above requirements of biometric information protection compliant with the international ISO/IEC 24745 standard. In our protocol, we present a novel modification of unlinkable fuzzy vault schemes that allows their connection with oblivious pseudo-random functions to achieve resilient protection against offline attacks crucial for the protection of biometric data. Our protocol is independent of the biometric modality and can be implemented based on the security of discrete logarithms as well as lattices. We provide an open-source implementation of both instantiations of our protocol which achieve real-time efficiency with transaction times of less than one second from the image capture to the completed key exchange.